Examining the relationship between students’ requirements and English for Islamic studies programs in Dar El Hadith El Hassania Institute, Rabat - Armouz, Youssef; Elotmani, Hanae (Research Journal in Advanced Humanities, 2023)
This study investigates ESP programs in the context of Islamic studies in Morocco. It examines the relevance of the English for Islamic Studies program implemented at Dar El Hadith El Hassania on students’ needs. To fulfill this purpose, a mixed-methods approach is adopted. A survey questionnaire and interviews are used to obtain reliable and scientific data. The survey findings indicated that the majority of participants have a great interest to learn English. Speaking and Grammar were rated as extremely important. The results obtained from students’ perceptions of the usefulness of the English course in meeting their needs reported that tasks related to Grammar and vocabulary were achieved to a satisfactory level.